2013
DOI: 10.2320/matertrans.m2013147
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of Temperature-Dependent Tensile Deformation and Fracture Features of Commercially Pure Titanium

Abstract: Tensile deformation and fracture behavior of a commercially pure (CP) titanium were investigated at different temperatures through mechanical tests, microstructural observations and fractal analyses. It was found that, with increasing temperature, the number and size of microvoids formed along shear bands (SBs) or at the intersections of SBs on the deformed specimen surface increase, and the fractal dimensions of the scanning profile at the surface near fracture increase correspondingly, and the ones measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…6c, 7d and 10a, namely, dense SBs are formed and the density of twins dramatically decreases. Such a phenomenon was also found in uniaxially tensioned CP Ti, for which the number of deformation twins reduces with increasing T [27]. The dramatic decrease in twin density weakens the interactions between twins and dislocations and thus leads to an obvious decrease in flow stress and weakens strain hardening ability.…”
Section: Deformation Features At Differentmentioning
confidence: 59%
“…6c, 7d and 10a, namely, dense SBs are formed and the density of twins dramatically decreases. Such a phenomenon was also found in uniaxially tensioned CP Ti, for which the number of deformation twins reduces with increasing T [27]. The dramatic decrease in twin density weakens the interactions between twins and dislocations and thus leads to an obvious decrease in flow stress and weakens strain hardening ability.…”
Section: Deformation Features At Differentmentioning
confidence: 59%
“…The results showed that the diffusion distance of Fe increases with the increase of heat treatment temperature. Ha and Hong [21] studied the deformation and fracture of titanium–stainless steel at different temperatures. Hai-tao et al [22] studied the effect of heat treatment on the microstructure and mechanical properties of titanium–steel explosive-rolling clad plates, which indicated that the diffusion of elements was increased with the increase of heat treatment temperature, and the TiC layer almost disappeared at 950°C.…”
Section: Introductionmentioning
confidence: 99%
“…The Ti/steel clad plate addresses this aspect. It not only ensures the perfect corrosion-resistance of Ti, but also provides excellent mechanical properties of ordinary steel plate, improves the service life of the equipment, and greatly reduces the production cost [ 1 , 2 , 3 , 4 , 5 , 6 ]. A few studies in this regard have been carried out on the manufacturing Ti/steel clad plate [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%